TANGGUNGJAWAB PELAKU USAHA APOTEK BUMI TERHADAP KONSUMEN ATAS PEREDARAN VAKSIN TIDAK MEMENUHI STANDAR FARMASI BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLIDUNGAN KONSUMEN - Antonio, Karen Liora (Rizky SH Mkn) (Fakultas Hukum Universitas Muhammadiyah Palu, 2022)
Vaccine circulation not only does not meet pharmaceutical standards, but is also an act that endangers human life if the contents of the vaccine are inappropriate or unclear. Using juridical normative. The nature of descriptive analytical research. Data analysis obtained qualitatively. Based on the results of the study, the regulation regarding restrictions on drug sales on vaccine circulation does not meet pharmaceutical standards in Indonesia, it has been stated in various laws and literature that have been set by the government. As stipulated in Article 1504 – 1512 of the Civil Code, in addition to Article 7 and 8 paragraph 3 and Article 24 UUPK, then Article 196 of Law Number 36 of 2014, Article 7, and finally Article 31 No. 9 of 2017 concerning Pharmacies. The legal responsibility of the Bumi pharmacy business actor for the distribution permit of vaccines in an effort to cure disease, this has been done by compensating consumers according to the value and price set. Obstacles and solutions to the responsibility of Bumi's pharmacy business to consumers including the poor control carried out by each product line that wants a distribution permit. It's easy to get vaccines as pharmacies that have been traded to the public. As a result, consumers feel disadvantaged because the vaccines obtained do not have pharmaceutical standards. The government's incompetence in supervising vaccines is increasingly selling freely without a permit so that consumers feel they don't get an official vaccine, because there are people who provide false and untrue information.